Pterostichus (Platysma) niger ... - Sundukov, Yurii N.; Novomodnyi, Evgeniy V. (Zenodo, 2022)
Pterostichus (Platysma) niger (Schaller, 1783) Material. Khabarovsk, 9.09.1970, A. Ryabukhin leg., 1♂; Korsakovo near Khabarovsk, 08.1997, E. Novomodnyi leg., 1♂. Distribution. A polyzonal transpalearctic species. In the Far East: Yakutia (south and the Lena River valley to Yakutsk in the north), Kamchatka (south and center), Amur Region (everywhere), Jewish Autonomous Region, Khabarovsky Region (valleys of the Amur and the Ussuri Rivers), Primorsky Region (not in the center and east of the Sikhote-Alin), Sakhalin (center and south), the Kuril Islands (Shumshu, Ketoi, Urup, Iturup). ... : Published as part of Sundukov, Yurii N. & Novomodnyi, Evgeniy V., 2022, Ground beetles (Coleoptera, Carabidae) of Khabarovsky Region in the collection of Grodekov Khabarovsk Regional Museum, pp. 570-593 in Amurian Zoological Journal XIV (4) on page 581, DOI: 10.33910/2686-9519-2022-14-4-570-593, http://zenodo.org/record/12815734 ...